Interventions in Improving Spiritual Well-Being: A Scooping Review - Alaidin, Makdum; Andriany, Megah; Dewi, Nur Setiawati (GLOBAL HEALTH SCIENCE GROUP, 2024)
Spiritual well-being has an important role for individuals in dealing with mental health problems and quality of life. The aim of this research is to explore various interventions to improve individual spiritual well-being to help overcome difficult situations, reduce stress and help achieve balance in life. Methodology: This research adopts an approachscoping review with the framework developed by Arksey and O'Malley. Research includes searching articles through databases Google Scholar and Spingerlink with the keyword